PERBANDINGAN RISIKO OBLIGASI SYARIAH DAN KONVENSIONAL DI INDONESIA - Evi Mutia; Heri Tamliqa; Wida Fadhlia; Suparno Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
Islamic and conventional bonds are two kinds of financial instruments that share in the Indonesian capital market. Islamic Bond (Sukuk) is bonds that the implementation based on the principles of Islamic law. Sukuk is not like other interest-based securities, but in conventional bond yields received one of them in the form of interest. The conventional bonds are based on debt instrument while the Sukuk financing is based on the equity method. The aim of this research is the comparative analysis of risk between sukuk and conventional bond in Indonesia by using model calculations Value at Risk (VaR) framework for the period 2010-2014. This study used various methods on analyze the data. The result indicates that there is a significant performance difference between Bonds and sukuk based on Yield toMaturity. YTM of sukuk is greater than conventional bonds. When compared risk with conventional bonds the sukuk stands better in these sensitivity measures and sukuk have a lower level of risk than conventional bonds.